Analysis of facilities management on inclusion education school in Batu City - Delora Jantung Amelia; Ichsan Anshory; Vivi Kurnia Herviani (CV Rezki Media, 2022)
Facilities and infrastructure in inclusive schools are the same as schools in general, friendly to all, equipped with accessibility that can help facilitate mobility and do not endanger students with special needs. This study aims to analyze the management of facilities and infrastructure at schools providing inclusive education in Batu City. The qualitative research design used a descriptive qualitative approach. The research was conducted in 3 schools providing inclusive education. Data was collected through observation, interviews, and documentation to the principal and special assistant teachers. The availability of facilities and infrastructure for schools that provide inclusive education is quite complete in Batu City, but still has many shortcomings such as lack of resource space, school accessibility and lack of supporting learning media for children with special needs. Inequality of learning media tools, the lack of books in the library, and the unavailability of an improper storage warehouse. With the lack of availability of learning facilities and infrastructure for children with special needs, it cannot be carried out optimally.